The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s41043-022-00344-4
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Childhood obesity risk increases with increased screen time: a systematic review and dose–response meta-analysis

Abstract: Background The role of screen time in promoting obesity among children has been reported in previous studies. However, the effects of different screen types and the dose–response association between screen time and obesity among children is not summarized yet. In the current meta-analysis we systematically summarized the association between obesity and screen time of different screen types in a dose–response analysis. Methods A systematic search fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 98 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…This minor difference may be attributable to the selection of the study population, as 52.7% of the study participants were male and 47.3% were female, and a similar finding in the US showed that there were no gender differences in weight status among children [21]. According to the other systematic review study, there were no appreciable differences in overweight between boys and girls; however, similar findings indicated that there were slight differences between males and females [22]. Our finding does not coincide with a cross-sectional study conducted among 5-17year-old school children although the prevalence of overweight was higher in girls than in boys (58% vs. 46%), respectively [23].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This minor difference may be attributable to the selection of the study population, as 52.7% of the study participants were male and 47.3% were female, and a similar finding in the US showed that there were no gender differences in weight status among children [21]. According to the other systematic review study, there were no appreciable differences in overweight between boys and girls; however, similar findings indicated that there were slight differences between males and females [22]. Our finding does not coincide with a cross-sectional study conducted among 5-17year-old school children although the prevalence of overweight was higher in girls than in boys (58% vs. 46%), respectively [23].…”
Section: Discussionmentioning
confidence: 67%
“…As technology continues to interactions the current culture of early screen exposure [21]. Furthermore number of studies reported that there are relationship between timing exposure to screen activities, television watching, food intake motivation, and snacking demeanor among children [22].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a significant increase in screen time among adolescents, which may have adverse effects on their health. Research has found a significant correlation between screen time and obesity among children [ 40 , 41 ]. Khan et al [ 42 ] found that excessive screen time of any type was associated with sleep difficulties among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, numerous studies highlight the relationship between obesity and excessive time spent online. Ramí rez-Coronel [44] suggests that the obesity-promoting effects of prolonged screen time may stem from its association with increased food intake. Additionally, Aghasi et al [45] conducted a meta-analysis revealing a significant positive correlation between high levels of Internet use and overweight/obesity compared to lower levels of use.…”
Section: Digital Influencesmentioning
confidence: 99%